Investigation of Plastering Effect in Casing-while-Drilling - A CFD Study - Ofei, T.N. (Institute of Physics Publishing, 2019)
In conventional oil and gas well drilling, filter cake builds up on the wellbore wall due to overbalance pressure which forces the drilling fluid into the rock formation and leaves solid particles on the wellbore wall. The presence of a filter cake is beneficial since it reduces fluid loss and damage to the formation. Plastering or "smearing" effect is a mechanical conditioning of a wellbore which is believed to enhance wellbore stability by packing any fractured zone with drilled-cuttings and fluid. This phenomenon is usually believed to occur in a narrow annular wellbore such as casing-while-drilling (CwD), where actual casing is used to drill and transmit both mechanical and hydraulic energy to the bit, rather than the usual conventional drillstring. In this study, a three-dimensional modelling and numerical simulation is carried out to examine the influence of particle size (drilled cuttings size) of 100 microns to 2000 microns and fluid type (water, oil-based mud, and water-based mud) on filter cake formation in a vertical wellbore. The simulation adopts the inhomogeneous Eulerian-Eulerian two-fluid model to solve the two-phase flow equations. The numerical model was set up to depict the subsurface conditions at moderate pressure and temperature of 13.8 MPa and 30Â°C respectively. The results showed that with the increase in particle size, the filter cake height increased marginally for all fluid types, where the percentage increment ranges from 1.3 to 2.6. Furthermore, filter cake thickness was high when water was used as the drilling fluid, whereas, the least filter cake height was recorded when oil-based mud was used. The filter cake formation on the vertical wellbore was therefore non-uniform for all scenarios. This study shows how useful numerical simulation can capture the physical mechanisms affecting plastering effect and optimise drilling parameters during casing-while drilling. Â© Published under licence by IOP Publishing Ltd.